Supporting teachers' development of Technological Pedagogical Content Knowledge: a whole school intervention - Garavito Munoz, E (2019)
There is a general consensus that teachers and schools need to use technology in the classroom to support their teaching practice and increase students' engagement, and this drives schools to spend an appreciable part of their available budget on technological tools. Furthermore, empirical research suggests that educational technology(such as Virtual Learning Environments (VLEs)) and the use of blended learning improve students' outcomes in different subjects. Other studies, too, indicate that increasing teachers' mastery and use of educational technology may also help to enhance students' engagement. However, teachers vary widely in their competence in applying and managing these technologies, with some scholars positing that issues such as cost, teachers' beliefs and a lack of appropriate training of teachers seriously undermine the benefits and value added of using digital technologies.